2013
DOI: 10.1177/1363461513503016
|View full text |Cite
|
Sign up to set email alerts
|

Frequent mental distress (FMD) in Irish Travellers: Discrimination and bereavement negatively influence mental health in the All Ireland Traveller Health Study

Abstract: Travellers are an indigenous minority group in Ireland, with poorer life expectancy and health status than the general population. Recent data have shown that Travellers are at increased risk of poor mental health and sequelae from same. We aimed to examine the associations between sociodemographic and lifestyle factors with poor mental health in Irish Travellers. A census survey of all Travellers was undertaken, with 8,492 enumerated families (80% response rate). A random subset of 1,796 adults completed an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Of these, the leading quantitative study calculated a Standardised Mortality Ratio for suicide amongst Travellers in Ireland, and reported an SMR of 6.6 for young adult males (Abdalla et al 2013). The qualitative studies focussed on aspects of mental illness and postvention themes and impacts of bereavement, grief and loss through suicide ((McGorrian et al 2013;Malone et al 2017;Tobin et al 2018;Millan & Smith, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the leading quantitative study calculated a Standardised Mortality Ratio for suicide amongst Travellers in Ireland, and reported an SMR of 6.6 for young adult males (Abdalla et al 2013). The qualitative studies focussed on aspects of mental illness and postvention themes and impacts of bereavement, grief and loss through suicide ((McGorrian et al 2013;Malone et al 2017;Tobin et al 2018;Millan & Smith, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst several review studies have looked at the health of Travellers, the focus has by and large been on physical health, vaccine uptake and outreach programmes with little emphasis on mental health and suicide. Yet, the findings from AITHS show high levels of mental ill-health, and frequent mental distress (FMD) has shown to be associated with key life events including experience of discrimination and bereavement (McGorrian et al 2013). There has been some research done by Mac Greil (1996Greil ( , 2010 which shows that Irish Travellers are exposed to the risk of discrimination on a daily basis in all aspects of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…We did, however, record the death as a bereavement variable in the analysis and found that this was an independent predictor of poor mental health for the respondent who completed the health status interview (McGorrian et al, 2013). Due to a change in legislation the onus to register a death now lies with the families in Ireland, and, if there are no probate issues in relation to a last will and testament, such registration may not take place.…”
Section: Retrospective and Prospective Linkage Studiesmentioning
confidence: 95%
“…Members of the Traveller community share a distinct culture based on nomadism and extended family structures, as well as a historically distinct language and economy, in addition to shared religious beliefs and value systems (Brack & Monaghan, 2007). Numerous interacting factors including lifestyle, cultural and socioeconomic factors, discrimination, and educational standards and low employment levels have meant that the Traveller community is a marginalized and socially excluded group within the country, with poorer health status and lower life expectancy than the general population (McGorrian et al., 2013; Van Hout, 2010) and a complicated relationship to bereavement, mourning, and grief.…”
Section: Introductionmentioning
confidence: 99%